Effect of Dextran Molar Mass on the Stability of Dextran-Nano-selenium and Its Application in the Preservation of South Bay Fish - Qing WANG; Zhou ZHOU; Lei LEI; Jianfang LI; Xinyue DENG; Jing ZHU; Jianqiu TU; Tao LIU (Shipin gongye ke-ji)
This study aimed to investigate the effect of dextran molar mass on the stability of Dex-SeNPs and the impact of Dex-SeNPs coating preservation solution on the storage and preservation of South Bay fish. Dex-SeNPs were prepared with dextran of different molar masses. The particle size, structure, and stability of Dex-SeNPs were characterized, and the antibacterial and preservation effects of Dex-SeNPs coating preservation solution prepared with the best molar mass on South Bay fish were analyzed. The results showed that with the increase of the molar mass of dextran, the average particle size of Dex-SeNPs gradually decreased. The average particle size of Dex-SeNPs prepared by dextran with a molar mass of 500 kg/mol was 132 nm, and the particle size was the smallest. UV-visible absorption spectroscopy, infrared spectroscopy, transmission electron microscopy analysis, and stability analysis further showed that the stability of Dex-SeNPs prepared by 500 kg/mol dextran was significantly improved. The interaction with SeNPs was the strongest, and the prepared nano-selenium had the best stability. The nano-selenium preservation coating solution prepared with a molar mass of 500 kg/mol dextran was used to test the storage and preservation of South Bay fish. On the 10th day of storage at 4 ℃, the sensory score of the 500 kg/mol-Dex-SeNPs group was significantly higher than that of the control group. The content of TVB-N, TBA, and the total number of colonies in the 500 kg/mol-Dex-SeNPs group were significantly lower than those in the control group, and the pH and texture were substantially better than those in the control group. This study laid a foundation for the application of dextran-nano-selenium in fish preservation.